Genotipagem do vírus da hepatite b em pacientes do Hospital Universitário da Universidade Federal de Sergipe - Sena, Ludmila Oliveira Carvalho (2010)
INTRODUCTION: The virus of hepatitis B was classified in eight genotypes that vary with geographic distribution, presenting different clinical manifestations and responses to anti-viral treatment. PURPOSES: This work intends to determine the prevalence of genotypes in Sergipe Brasil and evaluate them according to clinical and histopathological findings. METHODOLOGY: In a transversal search, were evaluated 97 patients, all of them AgHBs chronic porters, with traces of viral replication. From those patients, we got DNA s amplification in 43 samples, that formed the core to genotypical determination. Those were also evaluated on AgHBe positivity, viral load (CV) quantification, aminotransferases (ALT) and histological data. RESULTS: The genotypes A and F, were identified, with 35/43 (81.4%) of genotype A. Twenty Five from 43 patients (58.1%) presented abnormal ALT level, AgHBe negative (23/43 53.5%) and CV below 10.000 copies/ml (20/32 62.5%). In the patients presenting genotype A, 20/32 (62.5%) presented CV below 10,000 copies/ml, but in those with the genotype F, 5/7 (71.4%) presented CV above 10,000 copies/ml (p=0,101). There was no statistic difference between viral genotype and histological findings. CONCLUSION: In Sergipe, the genotypes A and F were found, but predominates the genotype A. Important differences were not found among the genotypes relatively to clinical and laboratorial findings.